Ethical Category of Virtue and the Concept of Freedom and Creativity of the Subject (Journal of Philosophy Culture and Political Science, 2020)
The article analyzes the ethical categories of virtue, decency, happiness, good, etc. from the point ofview of freedom, creativity of the subject and freedom of choice of values. The unity between the choiceof positive or negative values and the individual’s choice of moral preferences, such as moral duty, thecommon good, happiness is shown, representing a culture of freedom of choice. The understanding isbased on the Kantian statement on freedom as the essence of man, which forms his inner spiritual coreand its spiritual and moral content. It has, according to Kant, an a priori character. In other words, independentof and prior to any experience and which is created by man himself, it can be changed by him atwill. Kantian definition of virtue qua an internal moral duty, which has a character of a motive in human,is substantiated. The author comes to the conclusion about the nature of human values for granted andnot for existing and defines phenomenon of decency in existential that is, a behavioral manifestation ofvalues and motives. It is alleged that human freedom and its moral meaning cannot be explained fromcause-effect laws, as is described in the methodological approaches of utilitarianism theories, since theyare the primary premise of human existence.Key words: virtue, decency, the common good, happiness, due, existent, existing, rights andfreedom.